Functional analysis of nitric oxide in Musa sp. cv. Berangan during interaction with Fusarium oxysporum f. sp. cubense Tropical Race 4 - Mohd Nasir, Nurul Najihah (2018)
Nitric oxide (NO) is one of the important signalling molecules that regulates plant defence against pathogen attack. The mechanism of S-nitrosylation, one of the posttranslational modifications involving NO is not known during an interaction between Fusarium oxysporum f. sp. cubense Tropical Race 4 (FocTR4) and Musa spp. (banana). Hence, this study was carried out to investigate the effect of NO on Fusarium wilt progression in Berangan banana plants and to determine the S-nitrosothiol (SNO) content as well as the abundance of S-nitrosylated proteins. The Berangan banana roots that have been treated with NO donor, GSNO and NO scavenger, carboxy-ptio were inoculated with FocTR4 conidial suspension using root dip inoculation method. The disease severity index (DSI) was recorded based on the score obtained for leaf symptom index (LSI) and rhizome discoloration index (RDI). Pre-treatment of infected Berangan banana plants with GSNO resulted in lower DSI with LSI and RDI scores of 2 and 4, respectively in comparison with pre-treatment using carboxy-ptio where the DSI is higher with LSI and DSI scores of 5 and 7, respectively. The pretreatment with GSNO reduced the disease severity status of the Berangan banana plants from highly susceptible to susceptible. In order to determine the S-nitrosylation of Berangan banana proteome, protein extraction from Berangan banana tissues was first optimized for one-dimensional non-reducing SDS-PAGE analysis. Trichloroacetic acid-acetone (TCA) gave the highest concentration and quality of protein extract compared to phenol and phosphate buffer saline (PBS) extraction protocols. Using Saville-Griess assay, SNO content in infected Berangan banana plants pre-treated with GSNO were recorded at 96.99 μM mg-1 while in untreated plants, the SNO was recorded lower at 57.59 μM mg-1. As expected, prior removal of NO in infected Berangan banana plants which were pre-treated with carboxy-ptio resulted in the lowest SNO content at 48.82 μM mg-1. Consistent with the role of NO during nitrosative burst at the early phase of plant defence response, FocTR4 induced higher SNO formation in root protein extract at 2 hours post inoculation compared to 12 hours post inoculation. In relation to that, biotin switch assay showed that more protein were S-nitrosylated in response to FocTR4 compared to non-infected Berangan banana plants. Overall, findings from this study suggest that NO is involved in the basal defence mechanism of Berangan banana during an early interaction with FocTR4 through S-nitrosylation. This study adds value to the existing pool knowledge on the molecular mechanism behind the interaction between FocTR4 and banana.